2002
DOI: 10.1038/nrc904
|View full text |Cite
|
Sign up to set email alerts
|

c-MYC: more than just a matter of life and death

Abstract: Deregulated expression of c-MYC occurs in a broad range of human cancers and is often associated with poor prognosis, indicating a key role for this oncogene in tumour progression. However, as established human tumours often bear multiple genetic lesions, it is difficult to determine whether c-MYC is instrumental in the initiation/progression of the tumour, or indeed whether inactivating c-MYC would lead to tumour regression. Regulatable transgenic mouse models of oncogenesis have shed light on these issues an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
917
2
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,047 publications
(954 citation statements)
references
References 120 publications
23
917
2
12
Order By: Relevance
“…In Burkitt lymphoma, MYC overexpression is secondary to the translocation of heavy or light immunoglobulin chains genes at a distance of 100-150 kb upstream (Joos et al, 1992) or 300 kb downstream (Henglein et al, 1989;Zeidler et al, 1994) of MYC. MYC activation was also observed in invasive carcinomas that develop in various organs such as breast, prostate, stomach or colon (Pelengaris et al, 2002). This activation, which is generally related to a moderate level of amplification, is often found in poorly differentiated tumors (Nesbit et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In Burkitt lymphoma, MYC overexpression is secondary to the translocation of heavy or light immunoglobulin chains genes at a distance of 100-150 kb upstream (Joos et al, 1992) or 300 kb downstream (Henglein et al, 1989;Zeidler et al, 1994) of MYC. MYC activation was also observed in invasive carcinomas that develop in various organs such as breast, prostate, stomach or colon (Pelengaris et al, 2002). This activation, which is generally related to a moderate level of amplification, is often found in poorly differentiated tumors (Nesbit et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…In cooperation with E6 in HPV-infected keratinocytes, MYC may also activate the telomerase reverse transcription promoter (Veldman et al, 2003). Recent data have underlined the important role of MYC in the differentiation of skin epithelium (Pelengaris et al, 2002;Alonso and Fuchs, 2003). Through the depletion of integrin b (Waikel et al, 2001), MYC was found to act selectively on epidermal stem cells (Gandarillas and Watt, 1997), driving them into the transit amplification compartment and stimulating differentiation into interfollicular epidermis and sebocytes (Frye et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aberrant AID expression was capable of triggering accumulation of nucleotide alterations in the c-myc gene in cultured hepatoma-derived cells in vitro. It has been demonstrated that deregulation of c-myc has been implicated in the etiology of a wide variety of human cancers (Pelengaris et al, 2002). The deregulating mutations impact either on the c-myc gene itself or on upstream regulatory sequences, and point mutations or gene amplification of c-myc was reported in human HCC (Feitelson, 2006).…”
Section: Expression Of Aid In Human Hepatocytes Via Nf-jb Y Endo Et Almentioning
confidence: 99%
“…Dysregulation of c-myc induces cellular transformation in vitro and tumorigenesis in vivo (Pelengaris et al, 2002). In general, low levels of c-myc mRNA and protein are expressed in normally proliferating cells.…”
Section: Introductionmentioning
confidence: 99%